PENERAPAN DATABASE DI UMKM ROTI GAMBANG SA’ARINA MENGGUNAKAN MICROSOFT ACCESS - Permana, Idris; Ariyanto, Erika Estry; Oktavianus Tampubolon, Joshua Nathanael; Hanan, Hanan; Kuswandi, Elvina Damayanti (Yayasan Nuraini Ibrahim Mandiri, 2025)
Good data management is important to increase efficiency in UMKM, including Roti Gambang Sa’arina. Utilization of technology such as Microsoft Access in preparing databases helps speed up access to information, reduces inputs errors, and supports more precise decision-making. This research aims to design and implement a database system that suits the needs of Roti Gambang Sa’arina. Microsoft Access was chosen because i tis easy to use and flexible enough to manage data on a small to medium-scale business. The results show that Microsoft Access cam simplify data management, speed up information search, and increase data accuracy. It is hoped that this system can help Roti Gambang Sa’arina run their businesses more efficiently and competitively.